The Role of Agile Marketing in Reducing Marketing Crises: An Analytical Study of the Opinions of a Sample of Employees in Private Banks in Kirkuk Governorate / Iraq - برهان احمد داستان; ارسلان بايز لاسك (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
This study aims to analyze the relationship and the impact between Agile Marketing and its dimensions(Reducing Waste, Adaptive Ability, Communication, Reducing Costs, Continuous Innovation and Learning) and marketing crises represented by their stages(Pre-Crisis Stage, Stage During the Crisis, Post-Crisis Stage) private banks in Kirkuk Governorate- Iraq, A after reviewing a group of studies and literature, theoretical concepts were written and a model and hypotheses were built based on the dimensions of agile marketing and the stages of marketing crises, and based on the nature of the research and the objectives it seeks to achieve, the descriptive analytical approach has been relied upon. In order to collect data, the questionnaire was relied upon, and(120) questionnaires were distributed directly to the members of the community represented by employees in private banks in Kirkuk Governorate. After sorting and checking the received forms directly, the number of valid questionnaires for analysis reached (93). Several statistical methods were used, including arbitrators and Cronbach’s alpha, to ensure honesty and stability, the Correlation Coefficient, where a correlation coefficient is used to know the relationship between variables, as well as Regression Analysis, where regression analysis is used to clarify all effects and predict the special value between the study variables, all of them Within the programs (SPSS-26) and(Amos V.25). The results showed a positive correlation and effect between the dimensions and stages of the research variables. Based on the results of the research, a number of proposals were presented related to the need for departments, leaders and supervisors in banks to focus on adopting the dimensions of agile marketing in order to avoid them, adapt to them, and get out of marketing crises successfully.